Obstructive lingual thyroid - Gonzalez, Mario E. (Clin Case Rep, 2020)
Lingual thyroid should be considered in the differential diagnosis of any base of tongue mass. Examination may reveal worrisome obstructive findings. However, a majority of patients are hypothyroid and respond favorably to hormone replacement therapy upfront. Surgery is reserved for patients unresponsive to medical management or those with severe obstruction.